Do Judges Have Tastes for Discrimination? Evidence from Criminal Courts - Park, Kyung H. (The Review of Economics and Statistics, 2017)
Numerous studies find that criminal court judges issue racially disparate sentences, but whether these patterns reflect tastes for discrimination remains unclear. An alternative explanation is statistical discrimination, which implies that judges rely on race to predict a felon’s latent criminality in the absence of perfect information. This paper uses an empirical approach that distinguishes between taste-based and statistical discrimination. The intuition is that if the rank order of judicial incarceration rates depends on race, then this is symptomatic of taste-based discrimination. The rank-order test results imply that we cannot reject the null hypothesis of no taste-based discrimination.